Ecologia de Tropidurus torquatus (Squamata: Tropiduridae) no bioma Pampa, extremo sul do Brasil - Arruda, Jeferson Luis Steindorff de (2009)
Lizards are considered model organism in ecology, allowing the understanding of patterns and relations between organisms and environment. Tropidurus torquatus is a species with a broad distribution, with populations in different habitats and under diverse environmental pressures. However, the knowledge of diverse aspects of this species are unknown, specially in the subtropical region of the continent. These characteristics make the species in this study excellent to understand questions about geographic variation and environmental variable relations. Our purpose with this study is try to solve some questions that comprehend reproduction and growth from individuals of this specie from two populations, in the Pampa biome, in the south of Brazil. To elucidate the reproductive ecology questions, we collected 315 animals from a population localized in Alegrete/RS, between September of 2007 and August of 2008. The collected animals were dissected and their gonads were analyzed in the laboratory. Growth data were obtained from a study between December 2006 and December 2008, in Santo Antão locality, Santa Maria, Rio Grande do Sul. Every month the individuals were captured, measured, and the difference between the captures were used to calculate the growth rate. The reproductive period was between September and January, with eggs produce from October to January. Males reach the sexual maturity earlier and with smaller size than females. Females produces in average 6,21 eggs per clutch and not produces multiple clutch in the same reproductive period. Temperature, photoperiod, insolation, precipitation and humidity do not affect the reproductive period, but can cause more effect in growth rate. Adult males grow up more than females in summer. Both males and females decrease growth rate when there are less photoperiod, insolation and temperature at the winter. The decrease in growth rate during the winter, has as main consequence there are less animals reproducing in the following season after their birth. The smaller growth rate, late maturation, small reproductive period and eggs incubation are the main characteristics that make the south population different from the others in the tropical climate. Others characteristics like clutch size and eggs size, time of reproduction and offspring size seem to have less variation between populations in this species, and even between species of the genera Tropidurus. The data this study suggest that historic factors and phenotypic plasticity, in response to environment variables, act in this population, in the south of Brazil.